Investigation of sit-to-stand and stand-to-sit in an above knee amputee - Gao, Fan; Zhang, Fan; Huang, He (2011 Annual International Conference of the IEEE Engineering in Medicine and Biology Society, 2011)
The objective of this pilot study is twofold: 1) to extract key factors/features in sit-to-stand and stand-to-sit (STS) performed by an above knee (AK) amputee; 2) to propose a convenient way to quantify symmetry. One male unilateral transfemoral amputee participated in the pilot study. The subject was instructed to rise in a comfortable and natural manner and conduct a series of sit-to-stand, stand-to-sit. We simultaneously measured kinematics, kinetics and muscle activities. Principal component analysis (PCA) was used to reduce the dimension and identify modes and a convenient index of STS symmetry (slope of the major axis of the error ellipse) is proposed using the insole pressure sensors. Based on the preliminary results it is recommended that kinematics and kinetics in both the sagittal and frontal planes be considered for an AK amputee performing STS. The information might be useful for further research on amputee STS.